1996
DOI: 10.1159/000106889
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid P Component Level in Alzheimer's Disease

Abstract: Serum amyloid P component (AP) is a normal plasma constituent that is observed in senile plaques and neurofibrillary tangles in brains of Alzheimer''s disease (AD) patients. In this study we have evaluated the AP levels in sera of 16 patients with AD and in 16 control subjects by enzyme-linked immunosorbent assay. The AP level was 22.4 ± (SD) 7.0 µg/ml in the AD group and 34.4 ± (SD) 6.6 µg/ml in the control group. The AP level in the AD group was significantly lower than that of the control group (p < 0.01). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 10 publications
2
14
1
Order By: Relevance
“…However, assuming a normal increase in the incidence of AD with age, a high percentage of our centenarians with impaired cognitive performance will in all probability have AD. The results of a recent study by Nishiyama et al [17], reporting a decrease in serum concentration of SAP for 'probable AD' patients, therefore seem to be in disagreement with our findings. One explanation for this discrepancy, although unlikely, would be that only few of the centenarians with a MMSE ^24 have AD, or the inconsistency reflects the difference in the age of the individuals examined.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, assuming a normal increase in the incidence of AD with age, a high percentage of our centenarians with impaired cognitive performance will in all probability have AD. The results of a recent study by Nishiyama et al [17], reporting a decrease in serum concentration of SAP for 'probable AD' patients, therefore seem to be in disagreement with our findings. One explanation for this discrepancy, although unlikely, would be that only few of the centenarians with a MMSE ^24 have AD, or the inconsistency reflects the difference in the age of the individuals examined.…”
Section: Discussioncontrasting
confidence: 99%
“…The only connection that has been reported so far between SAP concentration and dementia has been SAP's involvement in AD [17,18]. However, assuming a normal increase in the incidence of AD with age, a high percentage of our centenarians with impaired cognitive performance will in all probability have AD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…154 This effect may be due to an alteration in Ab-binding proteins in AD patients. Previous studies have indicated that there may be alterations in the levels of proteins that attenuate Ab fibrillization, namely a2M 155 and SAP 156 in AD patients, although there are also conflicting data on this issue. It should be noted that polymorphism in the a2M gene may be associated with AD risk in some populations and may be influenced by family history (for example references [157][158][159][160][161][162] ), although these findings are controversial.…”
Section: Ab-binding Proteins In Blood Plasmamentioning
confidence: 99%
“…The results suggest that the deposition of AP in senile plaques and neurofibrillary tangles is not due to its overproduction. The production of AP by the liver (hepatocytes), Serum Proteome Analysis of Catatonia thought to be the only source, may be suppressed in AD patients [21].…”
Section: Serum Proteome Analysis Of Catatoniamentioning
confidence: 99%